In Vitro Pancreatic Lipase Inhibitor Activity of Mangifera foetida Leaves Extract - Aji, Oktira Roka; Hudaya, Riris Asyhar; Putri, Diah Asta (Jurnal Biodjati, 2021)
Obesity is a condition where there is excessive fat in the body. Weight loss can be accomplished by inhibiting fat absorption through the inhibition of pancreatic lipase activity, a key enzyme in fat metabolism. Natural products from plants contain various phytochemical compounds that can act as pancreatic lipase inhibitors. This research was conducted to determine the lipase inhibitor activity of the methanol extract of Mangifera foetida leaves. Mangifera foetida leaves were extracted and then the total phenolic and flavonoid levels were determined. The extract was tested for its ability to inhibit pancreatic lipase in vitro. The inhibitory activities of the extract and Orlistat were measured using p-nitrophenyl palmitate as a substrate at concentrations of 31.25, 62.5, 125, 250, and 500 Âµg/mL. The results showed that the extracts of young leaves (YL) and mature leaves (ML) contained phenol and flavonoid compounds. The IC50 values of young leaf extract (YL) and mature leaves (ML) were 45.22 and 35.50 Âµg/ml, respectively. In conclusion, the Mangifera foetida leaf extract can be promoted as a good source of anti-obesity compounds